التجارة الالكترونية وأهميتها في المعاملات المالية دراسة شرعية - مولود, عطا أحمد (Sulaimani Journal for Humanities, 2022)
This research aims to highlight the necessity of electronic commerce, with an explanation of the ease of carrying out the commercial process with the least costs and effort and the shortest time, and an explanation of the ruling on electronic commerce in Islamic jurisprudence. Also, electronic commerce transactions lead to the abandonment of all traditional means represented by the paper document after it was replaced by electronic documents, including adding another positive characteristic to electronic dealings. the importance of this research is to highlight the role of electronic commerce, the necessity of electronic commerce in this era and the extent to which it is facilitated in transactions and among the topics that are widely practiced among dealers in trade matters, with the most important characteristics, conditions and obstacles facing this type of modern commercial transactions. As for the research methodology, this research has used a descriptive theoretical study to trace the stages of that kind of trade, through most aspects and pictures of commodity exchange via the Internet. Through the research, results were reached, the most important of which is that electronic commerce has become an important tool for gaining money and wealth, and it has become a global trade in this era that cannot be ignored due to its necessity and importance, and this trade has become a reality that merchants and dealers must deal with accurately and safely, thus becoming a new technological revolution. It was not present in previous centuries, and it is considered one of the achievements of mankind, and an important tool in changing the pattern of economic life, and we know that this trade gains a benefit for both parties to the contract just like regular trade, so what is not a benefit in Sharia is not permissible to trade in and deal with, and this trade also has obstacles and challenges Must be resolved. As for the most important recommendations in this research, it is the necessity of Islamic researchers to write about this type of trade due to its importance, and governments should open centers in the country to develop qualified cadres for this industry, and intensify advanced educational and training programs in the field of information technology. Also, the state must work to develop Internet service by reducing the price and speed of communication to ensure the speed of dealing in this trade, and the state should thus pay attention to this trade so that it can keep pace with developed countries in the field of electronic commerce.